1998
DOI: 10.1080/10889869809351333
|View full text |Cite
|
Sign up to set email alerts
|

Organic Bulking Agents for Enhancing Oil Bioremediation in Soil

Abstract: Soil contaminated with oil is bioremediated by optimizing conditions for microbial activity. Often the question arises about the benefits of bulking with organic materials to improve soil conditions to enhance degradation of the less biodegradable or less bioavailable components. An investigation was undertaken in the laboratory with the objective of measuring the influence of bulking with dried plant material, bermudagrass, and alfalfa on the degradation of oily sludge added to soil. The oily sludge was dilut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Results demonstrated that the mulch causes no inhibition to seed germination (Guerin, 2020). Other studies have demonstrated the successful use of bulking agents, such as wood chips, to improve the agronomic properties and related attributes of contaminated soil (Chang & Weaver, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Results demonstrated that the mulch causes no inhibition to seed germination (Guerin, 2020). Other studies have demonstrated the successful use of bulking agents, such as wood chips, to improve the agronomic properties and related attributes of contaminated soil (Chang & Weaver, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…The use of organic amendments is a common practice to enhance pollutant degradation (Printz et al, 1995;Chang and Weaver, 1998), since they offer advantages allowing enhanced porosity of the system and other physical limitations. This study allowed us to select those variables and levels that were significant for enhancing TPH removal.…”
Section: Discussionmentioning
confidence: 99%
“…Hazards associated with the biodegradation process are divided into five groups: i) climatic conditions, ii) spilt oil physical and chemical properties, iii) soil characteristics, iv) microorganisms and their metabolic activity, and v) treatment strategy. These hazards were identified and assessed by performing a literature review (Margesin and Schinner 1999;Margesin and Schinner 2001;Filler et al 2006;Balba et al 1998;Mrozik et al 2003;Vidali 2001;Yang et al 2009;Atlas 1981;Fingas 2011;EPA 2004;Fernández-Luqueño et al 2011;Wania 1999;Liu et al 2006) and analysing previous bioremediation treatment case studies in the Arctic regions (Greenwood et al 2009;Margesin 2000;Masloboev and Evdokimova 2012;Evdokimova et al 2012;McCarthy et al 2004;Mohn and Stewart 2000;Sanscartier et al 2009;Chang and Weaver 1998;Walworth et al 2001;Walworth et al 2007;Zytner et al 2001;Whyte et al 1999;Paudyn et al 2008;Børresen and Rike 2007;Filler et al 2001;Couto et al 2014).…”
Section: Hazard Identification For Biodegradation Performancementioning
confidence: 99%